The Marginal and Average Propensities to Consume: Comment - Spraos, John (Quarterly Journal of Economics, 1955)
Journal Article The Marginal and Average Propensities to Consume: Comment Get access John Spraos John Spraos University of Sheffield, England Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 69, Issue 4, November 1955, Pages 644–645, https://doi.org/10.2307/1882003 Published: 01 November 1955